The Role of the Indonesian Waqf Board (BWI) in Productive Waqf in Gorontalo Province - Midu, Miranti; Halid, Fatmawati N.; Podungge, Syaifuddin; Thaidi, Hussein Azeemi Abdullah; Misbah, Ibah (Talaa : Journal of Islamic Finance, 2024)
The Indonesian Waqf Board (BWI) of Gorontalo Province plays an important role in the development of productive waqf which aims to improve the management and empowerment of waqf productively in Gorontalo. This research uses a scientific study research method with a descriptive qualitative approach. This research relies on secondary data obtained from various relevant literature sources, including journals, books, industry reports, and official documents from government agencies related to the role of Indonesian waqf (BWI) in productive waqf in Gorontalo Province. The results show that BWI Gorontalo has succeeded in improving productive waqf management through training programs, empowering nazir, and providing access to financing. The increase in IWN indicates progress in waqf management, and the positive impact on society has been seen through the distribution of waqf proceeds for social and economic needs.